Complications following surgery for adolescent idiopathic scoliosis over a 13-year period: a review of 84, 320 patients from the Scoliosis Research Society Morbidity and Mortality Database. (April 2020) - Kwan, Kenny Y. H.; Koh, Hui Y.; Blanke, Kathleen M.; Cheung, Kenneth M. C.
Abstract : Aims: The purpose of this study was to evaluate the incidence and analyze the trends of surgeon-reported complications following surgery for adolescent idiopathic scoliosis (AIS) over a 13-year period from the Scoliosis Research Society (SRS) Morbidity and Mortality database. Methods: All patients with AIS between ten and 18 years of age, entered into the SRS Morbidity and Mortality database between 2004 and 2016, were analyzed. All perioperative complications were evaluated for correlations with associated factors. Complication trends were analyzed by comparing the cohorts between 2004 to 2007 and 2013 to 2016. Results: Between 2004 and 2016, a total of 84, 320 patients were entered into the database. There were 1, 268 patients associated with complications, giving an overall complication rate of 1.5%. Death occurred in 12 patients (0.014%). The three most commonly reported complications were surgical site infection (SSI) (441 patients; 0.52%), new neurological deficit (293; 0.35%), and implant-related complications (172; 0.20%). There was a statistically significant but weak correlation between the occurrence of a SSI and the magnitude of the primary curve ( r = 0.227; p < 0.001), and blood loss in surgery ( r = 0.111; p = 0.038), while the occurrence of a new neurological deficit was correlated statistically significantly but weakly with age at surgery ( r = 0.147; p = 0.004) and magnitude of the primary curve ( r = 0.258; p < 0.001). The overall complication rate decreased from 4.95% during 2004 to 2007 to 0.98% during 2013 to 2016 (p = 0.023). Conclusion: An overall complication rate of 1.5% was found in our series after surgery for AIS, with a reduction of complication rates found in the second period of the analysis. Cite this article: Bone Joint J 2020;102-B(4):519–523.